Vulnerabilidades e patrimônio de famílias de crianças desnutridas: um estudo realizado no Centro de Recuperação e Educação Nutricional - CREN/SP - Nascimento, Célia Regina do (2008)
It is known that under-nourishment represents an important indicator of poverty, and that families of under-nourished children are exposed to multiple factors that affect their quality of life. This descriptive-exploratory study, with a quantitative and qualitative approach aimed to analyze the situation of vulnerability and identify the asset of the families of children that are part-time assisted by CREN Centro de Recuperação Nutricional, between 2005 and 2006 in São Paulo Vila Mariana. The methodology used in this study supported the development of a systematic work in social service at CREN, as the social evaluation based on the questionnaire created by Instituto de Estudos Especiais da Pontifícia Universidade Católica de São Paulo, in partnership with CREN, allowed the continuous characterization of the assisted under-nourished children´s families. The factors that turn these families more vulnerable and the resources they have - their asset, were taken in consideration. Through interview, questionnaires of social and economic characterization were applied to 42 assisted families at CREN. The results showed that families of under-nourished children part-time assisted by CREN were young, with low income, with a high number of children under 5 years-old, and with women as main breadwinners. The social, economic, and demographic characteristics, among others, confirmed the situation of high social vulnerability that these families experience. However, in the same context, it was noticed the presence of: a supportive social web, education, and predominance of biparental families. These characteristics are here defined as the asset of the families. Through this research, it was seen that when a social work considers the asset and situations of vulnerability in the beginning of the process, it is able to face the social reality in a more realistic way